The Fifteenth-Century Councils: Francisco de Vitoria, Melchor Cano, and Bartolomé Carranza - Izbicki, Thomas (Renaissance and Reformation / Renaissance et Réforme, 2019)
The Dominican theologian Francisco de Vitoria, founder of the School of Salamanca, was cautiously positive about general councils as useful to the church. However, he was not supportive of the strong conciliarism of the University of Paris. Vitoria’s successor at Salamanca, Melchor Cano, was much more a papalist, an opinion partially shared by Bartolomé Carranza, who attended the opening sessions of the Council of Trent (1545–63) and became archbishop of Toledo. Both Cano and Carranza rejected any claim to conciliar power over a reigning pope, although Carranza wrote more favourably about councils than did Cano. Their criticisms of the fifteenth-century councils of Constance (1414–18) and Basel (1431–49) foreshadowed the categorization of councils by Robert Bellarmine based on loyalty to the papacy. All of these theologians shared the belief that the ideal council was that of Ferrara–Florence (1438–45), which was summoned and directed by a pope.